2023
DOI: 10.1007/s00259-023-06147-x
|View full text |Cite
|
Sign up to set email alerts
|

EDB-FN targeted probes for the surgical navigation, radionuclide imaging, and therapy of thyroid cancer

Abstract: Extradomain B of bronectin (EDB-FN) is a promising diagnostic and therapeutic biomarker for thyroid cancer (TC). Here, we identi ed a high-a nity EDB-FN targeted peptide named EDBp, and developed three EDBp-based probes, Cy5-EDBp, [ 18 F]-EDBp and [ 177 Lu]-EDBp the surgical navigation, radionuclide imaging and therapy of TC. MethodsBased on the previously identi ed EDB-FN targeted peptide ZD2, the optimized EDB-FN targeted peptide EDBp was identi ed by using the alanine scan strategy. Three EDBp-based probes,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…EDBp was optimized from the classical EDB-FN-targeting peptide ZD2 by alanine scanning, and its a nity with EDB-FN substantially increased from 4.8 µM to 14 nM [21]. PET/CT imaging showed that the radiotracer [ 18 F]-EDBp had high accumulation in bilateral primary thyroid lesions and bone metastases in two patients with thyroid cancer [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EDBp was optimized from the classical EDB-FN-targeting peptide ZD2 by alanine scanning, and its a nity with EDB-FN substantially increased from 4.8 µM to 14 nM [21]. PET/CT imaging showed that the radiotracer [ 18 F]-EDBp had high accumulation in bilateral primary thyroid lesions and bone metastases in two patients with thyroid cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of the Peptides. The red uorescence peptide EDBp-Cy5 (chemical structure: AVRTSAD-PEG 4 -K-Cy5) and CG7C-Cy5 (chemical structure: CGGGGGGGC-Cy5) and the PET precursor peptide EDBp-NOTA (chemical structure: AVRTSAD-PEG 4 -K-NOTA) were designed by Feng et al [21]. (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34] Typically, DOTA/ NOTA chelators have been commonly utilized for the purpose of radionuclide complexation. 35 These chelators are characterized by their polydentate macrocyclic structures, which enable them to effectively accommodate di-and tri-valent metal ions through coordinative binding. Conjugation of macrocyclic structures capable of radionuclide chelation with the polymeric shell of nanoparticles would result in complex structures that require supplementary synthesis and purification procedures, thereby causing a significant increase in the production costs of a radiopharmaceutical compound.…”
Section: Introductionmentioning
confidence: 99%